Evaluation of the Predisposing Factors for Recurrent Respiratory Tract Infections in Iraqi Pediatric Patients. - Al-Hamdani, Fadya Yaqoob; Al-Mutawalli, Basma Zuheir (Al Mustansiriyah Journal of Pharmaceutical Sciences, 2014)
Recurrent respiratory tract infections are responsible for about 85% of all diseases in childhood, and are associated with significant morbidity and mortality. The aim of this study is to evaluate the main causes underlying recurrent respiratory tract infections in 176 pediatric patients aged 2 month to 4 year and weight from 4 to11 kg referred to the child center hospital and Al-sader hospital prospective study. All parents were given information sheet which then analyzed and the percentage of incidence of causes were recorded, we found that higher % related to many causes; mostly related to the parent like poor family education, mother carelessness, incomplete vaccination, other related to empirical diagnosis, and short course of treatment and type of antibiotic used. We conclud that the burden of respiratory tract infections in paediatrics is extremely high. Due to adequate diagnosis and causative therapies of these often recurrent respiratory tract infections bear substantial limits, preventive measures deserve priority.The mainstays are parent education, active immunizations strategies and nonspecific immunostimulation with bacterial products.